Efektivitas Antijamur Kombinasi Ekstrak Bajakah (Uncaria acida) dan Bandotan (Ageratum conyzoides) pada Mencit dengan Onikomikosis yang Terinfeksi Trichophyton rubrum - Nor Rezqiyatun Najhah; Mukhlis Rohmadi; Lilin Ika Nur Indahsari (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Onychomycosis is a fungal infection of the nail predominantly caused by Trichophyton rubrum and requires safer alternative therapies compared to synthetic antifungal agents. The combination of plant extracts may produce synergistic effects through interactions among bioactive compounds with complementary antifungal mechanisms. This study aimed to evaluate the effectiveness of a combined extract of Bajakah root (Uncaria acida) and Bandotan leaf (Ageratum conyzoides) as a topical therapy in T. rubrum–induced Balb/c mice. The selection of this combination was based on the presence of flavonoids, tannins, alkaloids, terpenoids, and saponins in both plants, which are theoretically associated with antifungal activity. Extracts were obtained by 96% ethanol maceration and formulated into ointments at concentrations of 25%, 50%, 75%, and 100%. Clinical parameters observed included periungual swelling, lesion diameter, nail discoloration, and nail brittleness. Phytochemical analysis confirmed the presence of major bioactive secondary metabolites in both extracts. The results demonstrated clinical improvement in all treatment groups, with the most pronounced effects observed at concentrations of 75–100%. Kruskal–Wallis analysis revealed significant differences among treatments (p < 0.05) for all parameters, which were further confirmed by Dunn’s post hoc test. Overall, the combined extracts of U. acida and A. conyzoides effectively reduced the severity of T. rubrum–induced onychomycosis and show potential as a natural antifungal candidate derived from local plant resources.